Emergence of new professions during the COVID-19 pandemic - L. G. Akhmaeva; D. V. Dolgopolov; A. I. Eremeeva (Вестник университета)
The article examines the changes that have occurred in communications in all spheres of human activity: in business, retail, education, culture, banking, which occurred due to the pandemic that began in the winter of 2020. The pandemic has spurred and accelerated the information technologies development, changed the attitude to working from home in general. The article focuses on the global changes that have occurred in the personnel direction. The change in interaction formats – the transition to an online environment, is analysed. Conclusions are drawn about the remote work format perception and about the change in the “remote work” concept perception by both employees, and managers in companies. The data on new emerged professions in this period, and on demanded professions on the online communications development wave, are given.